1995
DOI: 10.1073/pnas.92.19.8994
|View full text |Cite
|
Sign up to set email alerts
|

Single-site cleavage in the 5'-untranslated region of Leishmaniavirus RNA is mediated by the viral capsid protein.

Abstract: Leishmaniavirus (LRV) is a double-stranded RNA virus that persistently infects the protozoan parasite Leishmania. LRV produces a short RNA transcript, corresponding to the 5' end of positive-sense viral RNA, both in vivo and in in vitro polymerase assays. The short transcript is generated by a single site-specific cleavage event in the 5' untranslated region of the 5. The initial search for viruses in the protozoan parasite Leishmania was undertaken for the potential power these organisms might provide as mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Viral density was reported to affect the growth of the Giardia parasite, and in the case of Trichomonas, the presence of dsRNA was associated with phenotypic modifications of the infected cells (23,35,45,46). In the Leishmania virus, an endoribonuclease activity was demonstrated to be associated with the capsid protein (29,30). These data strongly suggested that extrachromosomal dsRNAs might interfere with the infected cells and that their encoded products might modulate the transcription level of the infected cells.…”
mentioning
confidence: 68%
“…Viral density was reported to affect the growth of the Giardia parasite, and in the case of Trichomonas, the presence of dsRNA was associated with phenotypic modifications of the infected cells (23,35,45,46). In the Leishmania virus, an endoribonuclease activity was demonstrated to be associated with the capsid protein (29,30). These data strongly suggested that extrachromosomal dsRNAs might interfere with the infected cells and that their encoded products might modulate the transcription level of the infected cells.…”
mentioning
confidence: 68%
“…Assays were performed as MacBeth and Patterson (1995) in 50 l reaction mixtures containing 10 l low-speed supernatant (2000 × g, 10 min) lysate from 1 to 10 × 10 6 sporozoites.…”
Section: Rna Polymerase Assaysmentioning
confidence: 99%
“…Virus-like particles produced in a recombinant baculovirus system expressing the LRV1-4 capsid gene were purified as previously described (5). Native LRV1-4 virion and recombinant virus-like particles are both functional in the in vitro cleavage assay and yield identical cleavage products (20). The RNA cleavage assays presented here were done with the recombinant LRV capsid, unless otherwise indicated.…”
Section: Methodsmentioning
confidence: 99%